Strategi pembelajaran PAI berbasis teknologi digital dalam meningkatkan motivasi belajar peserta didik - Adelia Salsabilah; Fitri Dwi Pratiwi; Eka Putri Cahyani; Ahmad Fuad Abdul (Jurnal Pendidikan Agama Islam, 2026)
The development of digital technology has had a significant impact on the world of education, including in Islamic Religious Education (PAI) learning. However, low student learning motivation remains a common problem due to the use of less varied and conventional learning methods. This study aims to examine digital technology-based PAI learning strategies to improve student learning motivation. The research method used was a qualitative approach with library research methods, namely through a review of books, scientific journals, research articles, and relevant academic sources. The results of the study indicate that the use of digital technologies such as audiovisual media, e-learning, bold learning platforms, and interactive applications can create PAI learning that is more engaging, interactive, and tailored to the characteristics of students in the digital era. Digital technology-based learning strategies also encourage increased interest, participation, and active student involvement in the learning process. Thus, the implementation of digital technology-based PAI learning strategies is effective in increasing student learning motivation.